Trace level monitoring of Cu(II) ion using CuS particles based membrane electrochemical sensor. Issue 6 (June 2021) - Gupta, Dipak Kumar; Neupane, Shova; Yadav, Harish Chand; Subedi, Vivek; Singh, Sanjay; Yadav, Ram Jeewan; Das, Anju Kumari; Yadav, Brahamdeo; Nakarmi, Krishna Badan; Karki, Nabin; Yadav, Amar Prasad
Abstract: Cu(II) monitoring is a matter of great interest to researchers due to its toxicity and adverse environmental effects. Among different methods for detecting Cu(II), ion-selective electrode (ISE) is more advantageous as they are low-cost, easy to fabricate, and highly selective. Here, we report a simple, inexpensive, and reproducible procedure for the fabrication of Cu(II) ion-selective electrodes using CuS particles and polyvinyl chloride (PVC) as a matrix. CuS particles, obtained by chemical precipitation, were characterized using X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, ultraviolet-visible spectroscopy (UV-Vis), scanning electron microscopy (SEM), and energy-dispersive X-Ray spectroscopy (EDX). Optimization of the membrane compositions was done to get a well-behaved sensor by varying amounts of CuS, PVC, and acetophenone (AP). A membrane composition of 0.4 g CuS, 0.5 g PVC, and 1.0 mL AP in 5.0 mL tetrahydrofuran (THF) gave a Nernstian slope of 27.31 mV per decade change of Cu(II) ion over a wide range of concentration down to 64 ppb (1 × 10 −6 M). The sensor gave a fast response time of 25 s, and it indicated the endpoint in a potentiometric titration of Cu(II) with standard EDTA solution. A pH-independent potential response was obtained in the pH 4.0–6.0. Abstract : Ion-selective electrode, Chemical precipitation, Copper sulfide, Nernstian slope, Potentiometric titration.